2006
DOI: 10.1097/01.ico.0000224648.74095.90
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Confocal Microscopy of Normal Conjunctiva and Conjunctivitis

Abstract: Confocal microscopy using near-infrared laser light is a useful new tool in the analysis of conjunctival tissue in vivo. It is a valuable aid in the differential diagnosis of conjunctival inflammation and thus may guide therapeutical decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
74
5
13

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(111 citation statements)
references
References 27 publications
19
74
5
13
Order By: Relevance
“…We used IVCM because this technique is minimally invasive, and it is effective in evaluating the histopathology of surface disease (Mastropasqua et al 2006;Messmer et al 2006;Hong et al 2010;Le et al 2010;Wakamatsu et al 2010;Zhu et al 2010) and the toxic effects of glaucoma therapy (Arici et al 2000;Messmer et al 2006;Ciancaglini et al 2008;Martone et al 2009;Bergonzi et al 2010). Our study showed that no changes occurred throughout followup in both controls and patients treated with preservative-free timolol; on the opposite, BAK-preserved eye drops were associated with signs of ocular surface inflammation (lower goblet cell density and epithelial irregularity) after 12 months of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We used IVCM because this technique is minimally invasive, and it is effective in evaluating the histopathology of surface disease (Mastropasqua et al 2006;Messmer et al 2006;Hong et al 2010;Le et al 2010;Wakamatsu et al 2010;Zhu et al 2010) and the toxic effects of glaucoma therapy (Arici et al 2000;Messmer et al 2006;Ciancaglini et al 2008;Martone et al 2009;Bergonzi et al 2010). Our study showed that no changes occurred throughout followup in both controls and patients treated with preservative-free timolol; on the opposite, BAK-preserved eye drops were associated with signs of ocular surface inflammation (lower goblet cell density and epithelial irregularity) after 12 months of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports of IVCM examination of the limbal palisades in normal and stem cell deficient patients has revealed the detailed in vivo morphology of this region thought to harbor epithelial stem cells. [15][16][17][18] The most notable characteristics are prominent ridge structures, circular focal stromal projections and limbal crypts residing between adjacent ridges at their base. Some or all of these structures were observed in healthy controls, but notably, the structures were present in an altered form in one case of aniridia.…”
Section: Discussionmentioning
confidence: 99%
“…The inferior limbal region was also examined by IVCM to assess morphology in the region of the limbal Palisades of Vogt. 15,16 Statistical analysis Mean BSCVA was calculated using the logmar scale, and logmar values were used for comparison of aniridia to controls. Visual acuity values were converted to the Snellen equivalent for reporting.…”
Section: Examinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the most reliable method for analyzing GCs in vivo is laser scanning confocal microscopy (LSCM), a noninvasive in vivo technology that evaluates the ocular surface tissues at the cellular level, providing a valuable method to identify and characterize GC morphology in different OSDs including glaucoma-related OSD (14)(15)(16). Nevertheless, to date, no study was specifically dedicated to determining the effects of the commercially available classes of glaucoma medications, and their regimens, on the density of conjunctival GCs in patients with glaucoma.…”
mentioning
confidence: 99%